Deming on the front lines: A systemic assessment of a retail organization in the Washington, DC metropolitan area and general recommendations for management - IVANOV, Sergey; TURCIOS, Evelin (Journal of Economics Library, 2025)
This paper is a case-study of a retail business, located in the Washington DC metropolitan area, based on one of the authors work experiences. The authors apply Deming’s organizational theory, as well as Harvey’s, Ivanov’s, and several other theorists’ ideas to evaluate the organizational system and work processes of this corporation at the front-line. Based on this study, the authors develop several general recommendations to management that may apply to all organizations facing similar issues, and also hope this paper continues the theoretical development of systemic organizational principles. Keywords. Organizational systems, W. Edwards Deming, Jerry B. Harvey, Organizational improvement, Management diseases. JEL. A10, A13, A14.